m6A Regulator-Mediated Methylation Modification Patterns and Tumor Microenvironment Cell-Infiltration Characterization in Head and Neck Cancer - Yang, Qinghui; Xu, Feng; Jian, Aiwen; Yu, Hongmei; Ye, Tao; Hu, Weiqi (Frontiers in Cell and Developmental Biology, 2022)
Background: Recently, RNA modifications have emerged as an essential epigenic regulators of gene expression. However, the mechanism of how RNA N6-methyladenosine (m6A) modification interact with tumor microenvironment (TME) infiltration remains obscure. Methods: 876 head and neck cancer samples considering 21 m6A regulators were included and analyzed to determine the m6A modification patterns. These modification patterns were then correlated with TME immune cell-infiltrating characteristics. A scoring system, the m6Ascore, was constructed using principal component analysis algorithms to quantify m6A modification of tumor. Results: Three m6A modification patterns were identified, with TME infiltrating characteristics highly consistent with tumors with three distinct immune phenotypes, including immune-inflamed, immune-exclude and immune-desert phenotypes. It was demonstrated that the identification of m6A modification patterns via m6Ascore could predict tumor progression, subtypes, TME stromal activity, variation of relevant genes and patient prognosis. Low m6Ascore, identified to be an inflamed phenotype, occurred to be associated with low stroma activity and tumor mutation burden, high survival probability, increased tumor neoantigen burden and enhanced response to anti-PD-1/L1 immunotherapy. The therapeutic advantages and clinical benefits of patients with low m6Ascore were further verified in two immunotherapy cohorts. Conclusion: This study identified the significant role the m6A modification played in the formation of TME characteristics. More comprehensive understanding of m6A modification patterns and its correlation with TME infiltration will contribute to the discovery of immunotherapy strategies with better efficacy.